Evolution in clinical presentation of inflammatory bowel disease over time at diagnosis: a multicenter cohort study. Issue 10 (October 2018) - Nahon, Stéphane; Ramtohul, Toulsie; Paupard, Thierry; Belhassan, Mehdi; Clair, Emeline; Abitbol, Vered
Abstract : Introduction: Delayed diagnosis of inflammatory bowel disease (IBD) has become a major issue, particularly in terms of the presence of nonspecific and heterogeneous clinical signs. This study aimed to identify changes over time in the epidemiological characteristics and clinical presentation of IBD in a French cohort. Patients and methods: Sociodemographic data from patients at three French hospitals (age, sex, country of origin, smoking habits) and characteristics of IBD [diagnostic delay, phenotype, location, first symptoms, first test suggesting diagnosis (endoscopy, imaging examination)] were collected in a computerized database (Focus_MICI). Four diagnostic time periods were assessed: <2000, 2000–2004, 2005–2009, and >2009. Results: Among the 926 patients analyzed, 638 (<2000, n =181; 2000–2004, n =104; 2005–2009, n =147; >2009, n =206) had Crohn's disease (CD) and 288 (<2000, n =54; 2000–2004, n =39; 2005–2009, n =80; >2009, n =115) had ulcerative colitis (UC). For CD, statistically significant differences over time were observed for (a) the first revealing disease symptom [more frequent abdominal pain vs. chronic diarrhea ( P <0.001)], (b) first investigation suggestive of diagnosis [more frequent computed tomography vs. colonoscopy ( P <0.001)], and (c) CD behavior [more frequent inflammatory vs. stricturing/penetrating forms ( P <0.001)]. No significant differences over time were observed for UC variables. Conclusion: In this large multicenter cohort study clinical diagnostic presentation of CD has changed over time. By contrast, there were no changes in the UC clinical presentation.